Comparative Effectiveness of Anticholinergic Therapy for OAB in Women. Issue 9 (September 2015) - Reynolds, W. Stuart; McPheeters, Melissa; Blume, Jeffery; Surawicz, Tanya; Worley, Katherine; Wang, Li; Hartmann, Katherine
<x xml:space="preserve">Abstract</x> ABSTRACT Behavior and lifestyle modifications are considered first-line therapy for overactive bladder (OAB). When these approaches are inadequate, the mainstay of second-line therapy is pharmacologic. The largest class of medications used for drug treatment is anticholinergic. Emerging evidence in a systematic review published in 2011 suggested that anticholinergic and other drugs used for OAB are often ineffective for long-term symptom management, with most patients discontinuing therapy within 6 months. Despite questionable data supporting use of anticholinergics for OAB, wider use of these agents was spurred by the 2013 US Food and Drug Administration approval of oxybutynin (Oxytrol) as an over-the-counter treatment for this condition as well as extensive direct-to-consumer advertising. The issue of effectiveness of drug therapy is of major concern to millions of women with OAB and to their health care providers. The aims of this systematic review and meta-analysis were first to examine available evidence from randomized clinical trials on outcomes of pharmacologic management of OAB in women and second to summarize comparative data from the active drug and placebo arms of randomized trials on the effectiveness of drugs for reducing urinary incontinence episodes and reducing voiding episodes. A search of 4 databases was conducted by multiple reviewers for original research published in English up to March 2014 on community-dwelling women with nonneurogenic OAB undergoing therapy with medications available in the United States. The database search included MEDLINE, EMBASE, Cumulative Index to Nursing and Allied Health Literature, and ClinicalTrials.gov. All studies were composed of at least 75% female subjects and had a minimal sample size of 50. Only randomized controlled trials were used for meta-analysis, and data on harms were collected from cohorts, case-control, and case series. The cumulative study population was composed of more than 27, 000 women receiving anticholinergic therapy with a median follow-up of 12 weeks (range, 2–52 weeks). Fifty randomized controlled trials from 144 candidate publications were identified; of the 50, one was of good quality, 38 fair, and 11 poor. Multiple team members extracted data independently, with secondary review of data entry performed to ensure quality and validity. Risk of bias was assessed in individual studies. Fixed-effects regression models were used for meta-analysis. The primary outcomes analyzed were the numbers of daily voids and urge incontinence episodes. Extended-release anticholinergics administered once daily reduced urge incontinence by 1.73 episodes per day (95% confidence interval [CI], 1.37–2.09) and voids by 2.06 per day (95% CI, 1.66–2.46) compared with baseline values of 2.79 (95% CI, 0.70–4.88) and 11.28 (95% CI, 7.77–14.80), respectively. Because placebo reduced urge incontinence episodes by 1.06 (95% CI, 0.7–1.42) and voids by 1.2 (95% CI, 0.72–1.67) per day, the net effect of the medication was modest. There was no superiority of any individual agent over another. Among the 50 studies, industry sponsorship accounted for 41 (98%) of the 42 studies reporting a source of funding. Meta-analysis of randomized controlled trials involving more than 27, 000 women suggests that anticholinergic management of OAB provides only a modest improvement in symptoms. The data do not allow definitive conclusions on the benefits of these drugs that can guide clinical decisions by patients with OAB and their health care providers.